SISTEM PEMINJAMAN DAN PENGEMBALIAN BUKU PERPUSTAKAAN KELILING BERBASIS WEB MENGGUNAKAN ALGORITMA STRING MATCHING PADA SUKU DINAS PERPUSTAKAAN DAN KEARSIPAN KOTA ADMINISTRASI JAKARTA UTARA - Rendi Sukmawan; Usman Gultom; Rachmawaty Haroen; Verdi Yasin (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2021)
The Mobile Library at the North Jakarta Administration City Library and Archives Office is a mobile library engaged in learning to increase readers' interest, especially in terms of learning. Where in the process of borrowing and returning books in the mobile library is still not well computerized and some processes are still done by hand and stored in catalog books. So that unorganized data is difficult to find, is often lost and makes it difficult for administrators to prepare reports. From the existing problems the writer designed and built a mobile library information system which is expected to be able to handle these problems. In looking for needs, system development is carried out through data collection methods by observation. In the system development method, the authors use object-oriented development methods with tools using the Unified Modeling Language (UML) in system analysis and design. Researchers use the PHP and MYSQL programming languages ​​as the database. It is hoped that with this mobile library information system, the processes involved in borrowing and returning books will be easier, because this mobile library information system can be accessed multi-user.